DESIGN OF QUEUE SYSTEMS IN TELECOMUNICATION and INFORMATION INDUSTRY USING FLEXIM 6.0 SIMULATION METHOD - Sulton Nur Hakim; Andika Julianto Putra; Sri Indrawati (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2020)
PT X is an information and communication company as well as a complete telecommunication service and network provider in Indonesia. In serving customer needs related to services, PT X has Plasa spread across 535 outlets throughout Indonesia until 2019.. Plasa is PT X outlet or place of service, which is fully managed by PT X or in cooperation with service partners. According to the explanation given by the Team Leader Plasa has service standards in serving customer needs including the standard customer service time is 10 minutes and the standard number of customers per CSR is 15 customers. But at PT X Yogyakarta the system actually only has one Customer Service to serve 50 customers and the service time sometimes exceeds the predetermined time standard. This resulted in quite long queues and long waiting times. The purpose of this research is to know the appropriate queue simulation model using flexim 6.0 so that waiting time at Plasa can be minimized. The average waiting time required by customers in the queuing system at Plasa is 3248.44 seconds and based on the alternatives that have been made, it can be seen that experiment 1 is the best, this is because the maximum waiting time achieved is better than experiments 2 and 3.